Sales coaching making the great leap from sales manager to sales coach - Richardson, Linda 1944- (McGraw-Hill, 2009)
Go from manager to coach--and motivate your staff to unprecedented success! Since the original publication of this classic guide, organizations have recognized that sales coaching is a sales manager's most important role. Now, author Linda Richardson has completely updated and revised Sales Coaching to include the latest tools and techniques, as well as a refined sales coaching process for increasing performance. Sales Coaching will help you make the essential transition from boss to coach so you can help salespeople achieve their goals. In this new role, you will empower your people to reach their highest potential by removing obstacles while fostering self and peer coaching, allowing direct reports to take responsibility for their own development. Richardson's broader objective is to help build and sustain a sales culture of continuous improvement and sales excellence. Inside you'll find a clear, practical, five-step approach to sales coaching that will result in dramatic changes in behavior. Sales Coaching includes brand new guidance on Maximizing technology Coaching more effectively Remote coaching Coaching in-the-action Quarterly coaching plans Richardson provides the skills and strategies you need to deliver feedback that changes behavior and strengthen relationships with your sales team. This new edition gives you everything you need to achieve your objectives and build a winning sales culture. You will watch members of your team reach performance heights they would not attain without your guidance. The results will benefit everyone--you, your staff, and ultimately your customers. The choice is yours: Be a manager who makes your salespeople do their jobs, or be a coach who helps your salespeople succeed.
Keywords: Sales management; Teams in the workplace; Ventes; Gestion; Équipes de travail; BUSINESS & ECONOMICS; Sales & Selling; Management